2013
DOI: 10.1128/iai.00004-13
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis Arginine Deiminase Modulates the Phenotype and Cytokine Secretion of Human Dendritic Cells by Depletion of Arginine and Formation of Ammonia

Abstract: bDepletion of arginine is a recognized strategy that pathogens use to evade immune effector mechanisms. Depletion depends on microbial enzymes such as arginases, which are considered virulence factors. The effect is mostly interpreted as being a consequence of successful competition with host enzymes for the substrate. However, both arginases and arginine deiminases (ADI) have been associated with pathogen virulence. Both deplete arginine, but their reaction products differ. An ADI has been implicated in the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 50 publications
4
29
1
Order By: Relevance
“…However, it remains uncertain as to which mediated the autophagy response, arginine deprivation or polyamine production. Yet, this is consistent with other reports demonstrating that L-arginine and L-arginine deprivation act as a sensor for autophagy arguably through mTOR signaling (Ban et al 2004;Yao et al 2008;Savaraj et al 2010;Wu et al 2011;Hsueh et al 2012;Banik et al 2013;Angcajas et al 2014). However, making the association less clear, the longer chain polyamine spermidine also acts as an inducer of autophagy but may not occur through mTOR signaling (Eisenberg et al 2009;Morselli et al 2009Morselli et al , 2011, yet it has been demonstrated to increase longevity, restore memory in various models through autophagy, and is elevated in centenarians (Eisenberg et al 2009;Morselli et al 2009Morselli et al , 2011Madeo et al 2010;Marino et al 2011;Minois et al 2011;Gupta et al 2013;Minarini et al 2013).…”
Section: Impact Of L-arginine and Polyamine On Autophagy And Inflammasupporting
confidence: 90%
“…However, it remains uncertain as to which mediated the autophagy response, arginine deprivation or polyamine production. Yet, this is consistent with other reports demonstrating that L-arginine and L-arginine deprivation act as a sensor for autophagy arguably through mTOR signaling (Ban et al 2004;Yao et al 2008;Savaraj et al 2010;Wu et al 2011;Hsueh et al 2012;Banik et al 2013;Angcajas et al 2014). However, making the association less clear, the longer chain polyamine spermidine also acts as an inducer of autophagy but may not occur through mTOR signaling (Eisenberg et al 2009;Morselli et al 2009Morselli et al , 2011, yet it has been demonstrated to increase longevity, restore memory in various models through autophagy, and is elevated in centenarians (Eisenberg et al 2009;Morselli et al 2009Morselli et al , 2011Madeo et al 2010;Marino et al 2011;Minois et al 2011;Gupta et al 2013;Minarini et al 2013).…”
Section: Impact Of L-arginine and Polyamine On Autophagy And Inflammasupporting
confidence: 90%
“…65 Decreased expression of genes related to cell proliferation has been observed following Giardia exposure to human colonic cell lines. 28,66 Furthermore, sodium-glucose transport proteins such as SGLT-1 appear to play a protective role in enterocyte apoptosis during the infection. Indeed, by enhancing epithelial SGLT-1 activity and therefore increasing glucose uptake, enterocytes try to protect against Giardia-induced apoptosis.…”
Section: Intestinal Permeability In Giardiasis: a Combination Of Tighmentioning
confidence: 99%
“…Previous studies have demonstrated that mast cell hyperplasia occurs in the late stages of a Giardia infection or following parasite clearance (20,21) and that eosinophil accumulation may occur in vivo in an isolate-dependent manner (22). Furthermore, G. duodenalis parasite products have been shown to modulate dendritic cell responses to lipopolysaccharide (23,24), while separate studies have demonstrated that intestinal epithelial cells (IECs) exposed to Giardia trophozoites produce a unique chemokine profile (25). The need to investigate G. duodenalis's ability to modulate its host's proinflammatory responses is now apparent due to data collected from in vivo animal and human studies.…”
Section: G Iardia Duodenalis (Syn G Intestinalis G Lamblia)mentioning
confidence: 99%